Epigenetic Age Acceleration of Stomach Adenocarcinoma Associated With Tumor Stemness Features, Immunoactivation, and Favorable Prognosis - Hong, Chunhong; Yang, Shaohua; Wang, Qiaojin; Zhang, Shiqiang; Wu, Wenhui; Chen, Jinyao; Zhong, Danhui; Li, Mingzhe; Li, Liang; Li, Jianfeng; Yu, Hong; Chen, Hong; et al. (Frontiers in Genetics, 2021)
Background: Abnormal DNA methylation (DNAm) age has been assumed to be an indicator for canceration and all-cause mortality. However, associations between the DNAm age and stomach adenocarcinoma (STAD) molecular features, and prognosis have not been systematically studied. Method: We calculated the DNAm age of 591 STAD and 115 normal stomach samples from TCGA and GEO database by using the Horvath’s clock model. Meanwhile, we used survival analysis to evaluate the prognostic value of DNAm age and epigenetic age acceleration shift. As sample size between the DNAmAge-ACC (DNAm age – chronological age > 0) and DNAmAge-DEC (DNAm age – chronological age < 0) groups does not match, we therefore performed weighted gene co-expression network analysis (WGCNA) to identify DNAm age associated gene modules and pathways. Finally, the association between DNAm age and molecular features was performed by correlation analysis. Results: DNAm age was significantly correlated with chronological age in normal stomach tissues (r = 0.85, P < 0.0001), but it was not associated with chronological age in STAD samples (r = 0.060, P = 0.2369). Compared with para-cancer tissues, the DNAm age of STAD tissues was significantly decreased. Meanwhile, chronological age in STAD samples was higher than DNAm age. Both DNAm age and epigenetic acceleration shift were associated with the prognosis of STAD patients. By using correlation analysis, we also found that DNAm age was associated with immunoactivation and stemness in STAD samples. Conclusion: In summary, epigenetic age acceleration of STAD was associated with tumor stemness, immunoactivation, and favourable prognosis.